Pillbug, Roly-Poly, Woodlouse Armadillidium vulgare (Latreille) (Malacostraca: Isopoda: Armadillidiidae) - Julie A. Franklin; Morgan A. Byron; Jennifer Gillett-Kaufman (EDIS)
The roly poly is an isopod, a type of non-insect arthropod also known as a terrestrial crustacean. It is called a roly-poly because it rolls into ball when disturbed. This defensive behavior also makes it look like a pill, which is why it is sometimes called a pillbug. In Europe, the name woodlouse is used for both roly polies and sowbugs because these arthropods are frequently found under logs. Roly polies are nocturnal, though they may be found during the day in the soil or under debris. They are beneficial in the garden or landscape. This 3-page fact sheet about the humble roly poly was written by Julie A. Franklin, Morgan A. Byron, and Jennifer Gillett-Kaufman and published by the UF Department of Entomology and Nematology, August 2015. (Photo by James Castner, University of Florida)